Validation of maternal cardiac output assessed by transthoracic echocardiography against pulmonary artery catheterization in severely ill pregnant women: prospective comparative study and systematic review. (28th November 2016) - Cornette, J.; Laker, S.; Jeffery, B.; Lombaard, H.; Alberts, A.; Rizopoulos, D.; Roos‐Hesselink, J. W.; Pattinson, R. C.
ABSTRACT: Objective: Most severe pregnancy complications are characterized by profound hemodynamic disturbances, thus there is a need for validated hemodynamic monitoring systems for pregnant women. Pulmonary artery catheterization (PAC) using thermodilution is the clinical gold standard for the measurement of cardiac output (CO), however this reference method is rarely performed owing to its invasive nature. Transthoracic echocardiography (TTE) allows non‐invasive determination of CO. We aimed to validate TTE against PAC for the determination of CO in severely ill pregnant women. Methods: This study consisted of a meta‐analysis combining data from a prospective study and a systematic review. The prospective arm was conducted in Pretoria, South Africa, in 2003. Women with severe pregnancy complications requiring invasive monitoring with PAC according to contemporary guidelines were included. TTE was performed within 15 min of PAC and the investigator was blinded to the PAC measurements. Comparative measurements were extracted from similar studies retrieved from a systematic review of the literature and added to a database. Simultaneous CO measurements by TTE and PAC were compared. Agreement between methods was assessed using Bland–Altman statistics and intraclass correlation coefficients (ICC). Results: Thirty‐four comparative measurements were included in the meta‐analysis. Mean CO values obtained by PAC and TTE were 7.39 L/min and 7.18 L/min, respectively. The bias was 0.21 L/min with lower and upper limits of agreement of –1.18 L/min and 1.60 L/min, percentage error was 19.1%, and ICC between the two methods was 0.94. Conclusions: CO measurements by TTE show excellent agreement with those obtained by PAC in pregnant women. Given its non‐invasive nature and availability, TTE could be considered as a reference for the validation of other CO techniques in pregnant women. Copyright © 2016 ISUOG. Published by John Wiley & Sons Ltd. RESUMEN Objetivo: Las complicaciones del embarazo más graves se caracterizan por trastornos hemodinámicos serios, debido a los cuales existe la necesidad de sistemas validados de monitorización hemodinámica para mujeres embarazadas. Aunque la cateterización de la arteria pulmonar (CAP) mediante termodilución es el patrón de referencia clínico para la medición del gasto cardíaco (GC), este método se usa con poca frecuencia debido a su naturaleza invasiva. La ecocardiografía transtorácica (ETT) permite la determinación no invasiva del GC. El objetivo de este estudio fue validar la ETT frente al CAP para determinar el GC en mujeres embarazadas gravemente enfermas. Métodos: Este estudio consistió en un metaanálisis que combinó datos de un estudio prospectivo y una revisión sistemática. El estudio prospectivo se llevó a cabo en Pretoria (Sudáfrica) en 2003. Se incluyeron mujeres con complicaciones graves en el embarazo que requerían una monitorización invasiva mediante CAP según las directrices de ese momento. Se realizó una ETT en un plazo de 15 minutos de haber realizado el CAP y el investigador no tuvo acceso a las mediciones del CAP. Las mediciones comparativas se extrajeron de estudios similares obtenidos a partir de una revisión sistemática de la literatura y se añadieron a una base de datos. Se compararon las mediciones simultáneas del GC mediante ETT y CAP. La concordancia entre métodos se evaluó a través del método estadístico de Bland‐Altman y de coeficientes de correlación intraclase (CCI). Resultados: Se incluyeron treinta y cuatro mediciones comparativas en el metaanálisis. Los valores medios del GC obtenidos mediante CAP y ETT fueron de 7, 39 l/min y 7.18 l/min, respectivamente. El sesgo fue de 0, 21 l/min, siendo los límites inferior y superior de la concordancia de −1, 18 l/min y 1.60 l/min; el error porcentual fue del 19, 1%, y el CCI entre ambos métodos fue de 0, 94. Conclusiones: Las mediciones del GC en mujeres embarazadas mediante ETT muestran una excelente concordancia con las obtenidas mediante CAP. Dada su naturaleza no invasiva y su disponibilidad, la ETT podría considerarse como referencia para la validación de otras técnicas relacionadas con el GC en mujeres embarazadas. 目的 : 大多数严重妊娠并发症的特点是发生严重血流动力学紊乱, 因此需要一个经过验证的孕妇血流动力学监测系统。采用热稀释法的肺动脉导管(pulmonary artery catheterization, PAC)是测定心输出量(cardiac output, CO)的临床金标准, 然而由于是有创性操作, 这种参考方法很少被采用。经胸超声心动图(transthoracic echocardiography, TTE)能够对CO进行无创性检查。我们的目的是验证危重症孕妇中与PAC相比TTE的CO检测结果。 方法 : 本研究将一项前瞻性研究和系统综述的数据合并进行meta分析。前瞻性研究于2003年在南非的比勒陀利亚进行。纳入根据目前的指南需要进行PAC有创性监测的发生严重妊娠并发症的患者。PAC 15 min内行TTE, 研究人员不知晓PAC检测结果。从文献系统综述检索到的相似研究中选取具有可比性的检测结果, 加入数据库。对TTE和PAC同时检测的CO结果进行比较。采用Bland‐Altman法和组内相关系数(intraclass correlation coefficients, ICC)评价两种方法的一致性。 结果 : meta分析中纳入34例具有可比性的检测结果。PAC和TTE得到的CO平均值分别为7.39 L/min和7.18 L/min。下限为–1.18 L/min、上限为1.60 L/min的一致性检验偏倚为0.21 L/min, 百分比误差为19.1%, 两种方法的ICC为0.94。 结论 : 孕妇中TTE的CO检测结果与PAC的CO检测结果具有高度一致性。由于具有无创性和易行性, TTE可以作为验证孕妇中其他CO技术的参考方法。 Abstract : This article's abstract has been translated into Spanish and Chinese. Follow the links from theabstract to view the translations.